2017
DOI: 10.1017/s0954579417000244
|View full text |Cite
|
Sign up to set email alerts
|

Circle of Security–Parenting: A randomized controlled trial in Head Start

Abstract: Although evidence shows that attachment insecurity and disorganization increase risk for the development of psychopathology (Fearon, Bakermans-Kranenburg, van IJzendoorn, Lapsley, & Roisman, 2010; Groh, Roisman, van IJzendoorn, Bakermans-Kranenburg, & Fearon, 2012), implementation challenges have precluded dissemination of attachment interventions on the broad scale at which they are needed. The Circle of Security–Parenting Intervention (COS-P; Cooper, Hoffman, & Powell, 2009), designed with broad implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 105 publications
(166 reference statements)
1
94
0
2
Order By: Relevance
“…The generalisability of the COS‐P program has been evident in previous studies that have concluded its efficacy in a number of settings and populations. For example, COS‐P has been successfully delivered to low‐income families in Head Start program (Cassidy et al., ); parents with infants under two years (Kohlhoff, Stein, Ha, & Mejaha, ); mothers in residential substance‐abuse treatment (Horton & Murray, ); and mothers with depressive symptoms (Maupin et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The generalisability of the COS‐P program has been evident in previous studies that have concluded its efficacy in a number of settings and populations. For example, COS‐P has been successfully delivered to low‐income families in Head Start program (Cassidy et al., ); parents with infants under two years (Kohlhoff, Stein, Ha, & Mejaha, ); mothers in residential substance‐abuse treatment (Horton & Murray, ); and mothers with depressive symptoms (Maupin et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Participants were 137 three‐ to five‐year‐old children ( M = 4.32 years; SD = 0.50; 79 female; 91 African American), recruited from four Head Start centers in low‐income Baltimore neighborhoods as part of a randomized controlled trial (RCT) of an attachment‐based parenting intervention (Cassidy et al., ). Participation was restricted to children and their mothers, who were also required to be the primary caregiver and to live with the child.…”
Section: Methodsmentioning
confidence: 99%
“…Cassidy et al. () found no main effects of intervention for child attachment, child executive functioning, or child behavior problems after a randomized controlled trial of 10 sessions of COS‐P with low‐income parents with children enrolled in Head Start programs. They did find that mothers who participated in COS‐P reported fewer unsupportive responses to child distress than did control mothers, and intervention effects emerged for some child outcomes moderated by mothers’ attachment style or depressive symptoms, suggesting that further work should explore if COS‐P might benefit some dyads and not others.…”
mentioning
confidence: 99%
“…Two small studies ( n = 15 in each) have reported different benefits with different samples: increased parent reflective functioning, decreased caregiving helplessness and reduced anger and rejection toward the child in an Australian sample (Kohlhoff, Stein, Ha, & Mehaja, 2016), and improved emotion regulation and more positive parent attributions and discipline practices in American mothers with substance‐abuse problems (Horton & Murray, ). Limitations of these studies (with the exception of the studies by Cassidy et al., ; Cassidy et al., ) include very small sample sizes, no control conditions, and no follow‐up assessments to see if gains are maintained. Furthermore, research has not yet examined whether characteristics of intervention facilitators are related to outcomes.…”
mentioning
confidence: 99%